PENGARUH MOTIF MENGAKSES CHANNEL YOUTUBE KELAS PAGI TERHADAP TINGKAT KEPUASAN MENONTON KOMUNITAS INSTAMEET PEKANBARU - Fadhil, Muhammad; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The progress of the mass media, especially the Youtube media, is currently growing rapidly, where Youtube has enabled the wider community to quickly and easily find out the various developments or information that is currently happening in the form of visual audio and video. Includes information on photography. Jakarta Morning Class is a Youtube channel that discusses information about photography with unique presentation features and easy to understand. In the theory of Uses and Gratification, the audience basically uses mass media based on certain motives, where the media are considered trying to meet the needs of the audience which is called an effective media. The aim of the researcher is to find out how much influence the motive of accessing the Youtube channel of the morning class on the satisfaction of watching at the Instameet Pekanbaru community.The method used in this study is an explanatory quantitative method, with data collection techniques through questionnaires. The location of the study was carried out in the Pekanbaru Sub-district. The number of samples of this study were 135 respondents. Sampling using simple random sampling technique. Researchers used simple linear regression analysis, to find out how much influence both variables. Processing of questionnaire data was carried out using the Windows version 20 Product and Service Solution (SPSS) program .Based on the results obtained from this study the Motif of watching Breakout Net Tv shows an effect of 14.5% on the satisfaction of watching Breakout Net Tv shows obtained by Students of Yamaha Pekanbaru Music School. The influence is included in the weak category and the remaining 85.5% is influenced by other variables not examined in this study. The results showed that the motive of watching the Morning Class Youtube Channel had an influence on the satisfaction of the Morning Class Youtube Channel, so that in this study Ha was accepted and H0 was rejected.Keyword: Channel Youtube, Instameet